Emoção, expressão e literatura: cenas de sartre e derrida para um estudo sobre o fenômeno da ausência e da morte - Rozangela Gontijo (2019)
Abstract This writing flowed into a theme about the phenomenon of absence and death in psychic life and art, especially in literary art. Starting from a study between the phenomenology of emotions in Jean-Paul Sartre and the expressive sign in Jacques Derrida, a scenario opened for the inscription of these two philosophers in a fold between phenomenology and semiology, between engagement and dissemination, having as scriptural support the terms of deconstruction. Literature has gained prominence at a time when it is about the unreality of the image and the silences of writing as phenomena of absence and death. Keywords: emotion, expression, literature, death, absence.